The Utilization of The Snakes and Ladders Game to Develop Early Reading Skills in Children Aged 3-4 Years - Endra Eka Kasih; Anik Lestariningrum; Isfauzi Hadi Nugroho (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
This study aims to describe the process and outcomes of using the snakes and ladders game to develop early reading skills in children aged 3-4 years. Early reading skills, including letter recognition and picture-word association, are foundational competencies that need to be introduced through enjoyable and age-appropriate learning media. This research employed a descriptive qualitative approach, conducted at Playgroup Laboratory School of Nusantara PGRI University Kediri, with data collected through observation, interviews, and documentation of learning activities from October 22 to November 6, 2025. The snakes and ladders game was adapted as a learning medium for letter recognition, implemented in sessions lasting 30-40 minutes at the end of each lesson. During the initial sessions, children demonstrated enthusiasm toward game-based activities such as rolling the dice and observing the pictures on the board, although their active involvement in naming letters remained uneven. This was attributed to the children's strong focus on the game mechanics itself and an insufficiently conducive classroom atmosphere. In subsequent sessions, notable improvements were observed in children's participation, their understanding of the game rules, their courage in pronouncing letters and picture names aloud, and their verbal interaction with the teacher. Teachers also reported measurable progress in children's letter recognition ability, their skill in matching pictures with flashcards, as well as improvements in concentration and self-confidence during learning activities. In conclusion, the snakes and ladders game proves to be an effective and promising learning medium, offering an enjoyable, concrete, and interactive approach to early reading development, while requiring careful classroom management and consistent teacher guidance to maximize its benefits.